Optical and electrochemical dual detection of β-lactoglobulin based on the methylene blue@copper-based metal-organic framework - Yuwei Wang; Jingyi Hong; Xinlong Wang; Liying Zhu; Ling Jiang (Food Materials Research, 2022)
β-lactoglobulin is an effective indicator of allergic protein detection. Herein, we produced a copper-based metal-organic framework coated with methylene blue, to realize the optical and electrochemical dual detection of β-lactoglobulin. Methylene blue was successfully encapsulated inside the copper-based metal-organic framework and released after addition of β-lactoglobulin. As the concentration of β-lactoglobulin increased, the intensity of the ultraviolet absorption band and the response current increased with the increasing concentration of methylene blue released from the copper-based metal-organic framework. The optical detection range is from 0.10 mg/mL to 10 mg/mL, and the detection limit is 0.10 mg/mL. The electrochemical detection range is from 1.0 × 10−7 mg/mL to 8.0 × 10−7 mg/mL, the detection limit is 2.0 × 10−8 mg/mL. The dual detection strategy, with no interfere with each other, played a synergetic role in the quick qualitative and precise quantitative analyses of β-lactoglobulin in a wide range of applications.